TRANSLATION PROCEDURES IN INDONESIAN-ENGLISH DENNY JA’S ESSAY POEM NAGA SERIBU WAJAH AND ITS ENGLISH TRANSLATION - Muh. Kholiq; Anggi Ratna Purwanti (UG Journal, 2022)
Poem is the common text translated from one language to other languages. The meaning and the beauty of its structure made the other different languages reader is interested in reading the poem in their native languages. The aim of this research is to find out translation procedures in Denny JA’s Essay Poem “Naga Seribu Wajah” . The method used in this research is qualitative descriptive method. The result of the research showed that the researcher found 17 data in Denny JA’s essay poem Naga Seribu Wajah namely cultural equivalent, descriptive, synonymy, recognized translation, compensation, expansion, and paraphrase. Paraphrase procedure has the most data meanwhile descriptive and compensation have only one data each.